2020
DOI: 10.13189/ujer.2020.080552
|View full text |Cite
|
Sign up to set email alerts
|

‎Developing a Scale for Creative Teaching Practices of Faculty Members at King Faisal ‎University‎

Abstract: Higher education is considered the center of scientific and social progress, because it qualifies individuals to serve society in various fields of life. Therefore, the faculty member has become the main pillar in building future generations, so his energies should be blown to make his teaching practices innovative, distinctive and creative. This study aims to develop a scale of creative university teaching practices at King Faisal University, and to know the degree of reliance of faculty members on creative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…From 33 articles, a total of 14 studies focused on China (Chang et al, 2021;Chen & Yuan, 2021;Cheung & Mok, 2018;Chung & Chen, 2018;Deng et al, 2020;Huang et al, 2019;Jin et al, 2021;Ke et al, 2020;Li & Li, 2019;Liu et al, 2020aLiu et al, , 2020bNiu et al, 2017;Wang & Kokotsaki, 2018;Xiong et al, 2020), 3 on Turkey (Atabek, 2020;Akyildiz & Celik, 2020;Kandemir et al, 2019), 2 on Saudi Arabia (Azeem et al, 2019;Mahmoud Alali, 2020), 2 on Europe (NemerAitski & Heinla, 2020;Sliogeriene & Valunaite-Oleskeviciene, 2017), 2 on Indonesian (Dwiningrum et al, 2020;Fitriah, 2018) and 2 on the United States (Anderson et al, 2021;Robinson et al, 2018). In the meanwhile, each research study focused on Korea.…”
Section: Background Of the Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…From 33 articles, a total of 14 studies focused on China (Chang et al, 2021;Chen & Yuan, 2021;Cheung & Mok, 2018;Chung & Chen, 2018;Deng et al, 2020;Huang et al, 2019;Jin et al, 2021;Ke et al, 2020;Li & Li, 2019;Liu et al, 2020aLiu et al, , 2020bNiu et al, 2017;Wang & Kokotsaki, 2018;Xiong et al, 2020), 3 on Turkey (Atabek, 2020;Akyildiz & Celik, 2020;Kandemir et al, 2019), 2 on Saudi Arabia (Azeem et al, 2019;Mahmoud Alali, 2020), 2 on Europe (NemerAitski & Heinla, 2020;Sliogeriene & Valunaite-Oleskeviciene, 2017), 2 on Indonesian (Dwiningrum et al, 2020;Fitriah, 2018) and 2 on the United States (Anderson et al, 2021;Robinson et al, 2018). In the meanwhile, each research study focused on Korea.…”
Section: Background Of the Selected Studiesmentioning
confidence: 99%
“…In terms of publication year, 3 papers were released in 2017 (Cayirdag, 2017;Niu et al, 2017;Sliogeriene & Valunaite-Oleskeviciene, 2017), 7 studies were published in 2018 (Barajas & Frossard, 2018;Cheung & Mok, 2018;Chung & Chen, 2018;Fitriah, 2018;Harris & de Bruin, 2018;Robinson et al, 2018;Wang & Kokotsaki, 2018), 6 studies were published in 2019 (Azeem et al, 2019;Huang et al, 2019;Kandemir et al, 2019;Li & Li, 2019;So & Hu, 2019), 11 studies were published in 2020 (Akyildiz & Celik, 2020;Atabek, 2020;Deng et al, 2020;Dwiningrum et al, 2020;Ke et al, 2020;Liu et al, 2020aLiu et al, , 2020bMahmoud Alali, 2020;NemerAitski & Heinla, 2020;Xiong et al, 2020) and 5 studies were published in 2021 (Abdullah et al, 2021;Amzaleg & Masry-Herzallah, 2021;Anderson et al, 2021;Chang et al, 2021;Chen & Yuan, 2021;Jin et al, 2021). The year 2020 was the most frequent year of publication.…”
Section: Background Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies conducted on the influence of gender on teachers teaching for creativity indicated a significant influence on teachers' teaching for creativity (Alali, 2020;Chang et al, 2021). Their studies showed that male teachers had higher creative teaching mean scores than female teachers.…”
Section: Discussionmentioning
confidence: 99%
“…This is also in line with Mohd Nor et al ( 2020) who stated that engaging students with the teaching and learning process was one of the class management elements of outstanding lecturers of Islamic education in polytechnics. Creative teaching also required teaching strategies that related lessons to real life and students 'experiences ( (Horng et al 2005;Mahmoud Alali 2020) This allowed students to think and generate their ideas to further increase their involvement in the teaching process.…”
Section: Discussionmentioning
confidence: 99%